Lists, Narratives, and Archives of Intangible Heritage: The Politics of Digital Re-enactments - Pietrobruno, Sheenagh (Intermédialités / Intermediality, 2016)
Intangible heritage is re-enacted through its repeated performance on UNESCO’s websites and YouTube. This re-enactment via media technologies takes shape through narratives, lists, and archives. The political concerns—notably, issues of authority—surrounding the formation of narratives, lists, and archives may nonetheless counter one another. Political underpinnings surface through the material technologies of these media forms as well as the context in which they are situated and circulate. Narratives, lists, and archives in divergent digital environments intertwine with heritage content to produce competing political values that such re-enactments can assume.